RURAL FARMERS’ LIVELIHOOD VULNERABILITY TO CLIMATE CHANGE EFFECTS: THE CASE OF DODOTA DISTRICT, ARSI ZONE, OROMIA, ETHIOPIA - EDAO, SHALO SHUMI; HIRPHA, HURGESA HUNDERA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Climate change has wide-reaching effects on the agrarian communities like Ethiopia since its dominant economy, agriculture, is vulnerable to climate extreme events. The conditions largely undermine the life system of the rural farming communities. Thus, this study examines livelihood vulnerability of rural farming communities to climate change effects in Dodota District, Arsi Zone, Oromia, Ethiopia. Data for this study was acquired from households of 360 selected using systematic random sampling. Key informant interviews, group discussion, and semi-structured household interviews were used for generating primary data relevant to this study. Vulnerability indices, descriptive statistics and ordinal logistic regression were applied for analysis of generated data. The results of vulnerability indices have shown that the vulnerability of farmers’ livelihoods to the effects of climate change was moderate. At household level, it has been revealed that about three fourth of the respondents participated in the study were classified as highly (50%) and moderately (24%) vulnerable to effects of climate change while for the remaining 18% and 8% of respondents, the vulnerability was low and very high respectively. Similarly, the ordinal logistic regression analysis result revealed that access to forage, occurrence of natural hazards, access to water bodies, land cultivation, oxen to plow, access to irrigation, access to adequate extension service and access to agricultural inputs have a significant relationship with climate change effects on farmers’ livelihood. Thus, it has been suggested that livelihood diversification is feasible strategy to reduce vulnerability of the households as there are rivers in the local areas.